How can the for-profit and non-profit sectors work in integrative, development cross-sector partnerships to contribute to the sustainable development goals? - Corbishley, Elizabeth (2016)
The purpose of this paper is to explore how the for-profit and non-profit sectors can work together in cross-sector partnerships (XSPs) to contribute towards the sustainable development goals (SDGs). The SDGs are indicative of the growing discourse around for-profit sector involvement in development, a discourse also evident in government policies and donor requests for funding. The paper investigates whether there is a difference between this discourse and reality.